Climatic history from early Weichselian (MIS 5D-C) valley-fill deposits and associated factors for basin sedimentation, mainland Kachchh, western India. (30th December 2022) - Dabhi, Madhavi; Chavan, Anil; Thakkar, Adarsh; Chauhan, Gaurav; Bhagora, Rakesh; Chauhan, Naveen; Shukla, Anil D.; Bhandari, Subhash
Abstract: Ephemeral fluvial systems in the dryland region of Kachchh are susceptible to climatic fluctuations. An increase in Indian Summer Monsoon Intensity (ISM) is responsible for the aggradation of sediments as valley-fill deposits in the river basins. In the present study sedimentological, chronometric, and geochemical analysis on the fluvial terrace sequences of Nirona and Bhukhi river basins are being used to interpret southwest summer monsoon variability from MIS 5D-5C along with the fluvial response to local tectonics. The sediment record indicates increased ISM precipitation from ∼110ka to ∼90ka, which corresponds to the MIS 5D to MIS 5C (Interstadial stage). The ISM became progressively weaker during the MIS-5B (stadial stage), leading to present-day arid conditions. The climatic factors weakened along with an interplay of local tectonics, leading to present-day conditions of bedrock incision.